If in an AP, Tm=n, Tn=m, prove d=-1.
Answers
Answered by
9
We know that nth term of an AP an = a + (n - 1) * d.
Now,
Given Tm = n.
= > a + (m - 1) * d = n ------- (1)
Given Tn = m.
= > a + (n - 1) * d = m ------ (2)
Now,
On subtracting, we get
= > (m - 1) * d - (n - 1) * d = n - m
= > d(m - 1 - n + 1) = n - m
= > d(m - n) = n - m
= > d = (n - m)/(m - n)
= > d = -(m - n)/(m - n)
= > d = -1.
Hope this helps!
Answered by
0
Answer:
Please refer to attachment
Step-by-step explanation:
using formula for d
then
taking out -1 common from numerator
then
both numerator and denominator gets cancel
and -1 remains
hence proved.
Attachments:
![](https://hi-static.z-dn.net/files/d57/9ce58c489538d7020617b8acb921bd4e.jpg)
Similar questions